2015
DOI: 10.1002/2014jb011265
|View full text |Cite
|
Sign up to set email alerts
|

Fluid accumulation along the Costa Rica subduction thrust and development of the seismogenic zone

Abstract: In 2011 we acquired an 11 × 55 km, 3-D seismic reflection volume across the Costa Rica margin, NW of the Osa Peninsula, to accurately image the subduction thrust in 3-D, to examine fault zone properties, and to infer the hydrogeology that controls fluid accumulation along the thrust. Following processing to remove water column multiples, noise, and acquisition artifacts, we constructed a 3-D seismic velocity model for Kirchhoff prestack depth migration imaging. Images of the plate boundary thrust show high-ref… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
84
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 70 publications
(88 citation statements)
references
References 76 publications
4
84
0
Order By: Relevance
“…With the Structures From the 2-D Seismic Profile BGR99-7 at Site U1380 Normal faulting is supported by the structure of the fault zones and normal fault stress regime observed from the drilled cores [Harris et al, 2013b] and is also consistent with the dense pattern of interpreted normal faults in the outer shelf based on multibeam bathymetry, backscatter, and 3-D seismic data [Kluesner et al, 2013;Bangs et al, 2015Bangs et al, , 2016. The missing material (800 6 70 m) across the MSR (section 5.1) could possibly all be due to normal fault offset (250 6 70 m) with no mass movement.…”
Section: Integration Of Resultssupporting
confidence: 58%
“…With the Structures From the 2-D Seismic Profile BGR99-7 at Site U1380 Normal faulting is supported by the structure of the fault zones and normal fault stress regime observed from the drilled cores [Harris et al, 2013b] and is also consistent with the dense pattern of interpreted normal faults in the outer shelf based on multibeam bathymetry, backscatter, and 3-D seismic data [Kluesner et al, 2013;Bangs et al, 2015Bangs et al, , 2016. The missing material (800 6 70 m) across the MSR (section 5.1) could possibly all be due to normal fault offset (250 6 70 m) with no mass movement.…”
Section: Integration Of Resultssupporting
confidence: 58%
“…Kodaira et al 2002;Abers 2005;Eberhardt-Phillips and Reyners 1999;Song et al 2009) thought to represent fluid-rich low-permeability SISZ. In a profile across the Costa Rica subduction margin, Bangs et al (2015) found a high-reflectivity interface extending to depths of c. 6 km, implying an overpressured fluid-rich interface drained by arrays of fluid-rich faults cutting through the hanging wall. MT electrical imaging provides additional constraints on fluid content.…”
Section: Tensile Overpressure Compartments Along Subduction Interfacesmentioning
confidence: 96%
“…Bangs et al (2015) also reported this reflective subduction channel farther southeast along the Costa Rica subduction zone; in a volume of three-dimensional seismic images they showed (2004) proposed a generic model of subduction erosion, in which a zone of hydrofracturing caused by high pore pressure fragments at the base of the overriding plate and facilitates removal of material in the subduction channel. Kimura et al (2012) quantitatively estimated the distribution of high pore fluid pressure in the Japan Trench by using a thermal model and considering the dehydration kinetics of opal-A to quartz and the transformation of smectite to illite; their results suggest that dehydration of underthrust sediments takes place at a distance of 40-80 km from the trench and peaks at 50-60 km landward of the trench axis.…”
Section: Reflective Zonementioning
confidence: 97%